Exploring new horizons: a comprehensive look into ACI Logistics Limited's (Shwapno) recruitment and selection process - Islam, Syed Ashikul (Brac University, 2024)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2023.